Economic Development Justice: The Role of Zakat, Infaq, Shadaqah (ZIS) Institutions in the Covid-19 Pandemic Era - Naerul Edwin Kiky Aprianto (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
In December 2019, the world was rocked by the coronavirus outbreak, the virus first appeared in the Chinese city of Wuhan. The impact of the Covid-19 virus is not only felt in China, but other countries including Indonesia have felt the shock. The impact caused by the corona virus is multidimensional, social, political, educational, as well as health and economic, where to overcome this impact requires good cooperation between the government, the community and ZIS fund management institutions optimally in order to contribute to handling Covid-19. Islamic social finance is very important and beneficial because it helps many people's difficulties. From this, the purpose of this article is to analyze the roles, prospects, opportunities and challenges of ZIS Management Institutions against the Covid-19 pandemic. This research uses qualitative descriptive method, which is research that uses qualitative data and then described descriptively. This study uses secondary data sources, where researchers can obtain data from existing sources, namely websites, journals, newspapers, financial reports, and books. In this study using a literature study instrument that aims to reveal various theories related to the problems studied, literature studies can also be used as input and basis in explaining how the implementation and mechanism of zakat distribution in dealing with the Covid-19 pandemic, so that it was found that ZIS institutions play an important role in building economic justice, especially acting as a social safety net.